Prevalence of Communicable Diseases and Causes of Variability Among Secondary Schools in Kisumu County, Kenya (Global Journal of Medical Research, 2015)
Prevalence of communicable diseases, which account for millions of school lost days a year, among secondary school students in Kisumu County is unknown. The number of secondary schools with school health facilities is unknown, and there is no indication from Kenya's Health Sector Strategic Plan, 2012-2017 that establishment of school health facilities will be given priority as an intervention. The overall objective of this study was to examine causes of variability in communicable disease prevalence rates among secondary schools in Kisumu County, Kenya. In order to achieve the overall objective, the following were the specific objectives: to determine prevalence rates of communicable diseases among secondary students in Kisumu County; to determine the cause of variability in communicable disease prevalence rates among students; and to evaluate public health intervention programs for optimal use in secondary schools. Survey, Correlational and Evaluation research designs were used for the three objectives respectively.